Structural analysis on flexibility training in men's artistic gymnastics/Análisis estructural sobre el entrenamiento de la flexibilidad en gimnasia artística masculina - Ninfa Julissa Gálvez Eras (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The importance and transcendence of each variable that influences flexibility training in gymnasts, evaluated by specialists, could be modeled prospectively to consider medium and long term decisions related to the training management process. Knowing the implications and level of importance of each variable of interest could optimize sport preparation, being structural analysis a tool to achieve this goal. The objective of this work is to determine key variables on flexibility training in men's artistic gymnastics; it is based on a prospective research of qualitative analysis, applying matrices that interrelated several variables of importance, delimiting in the future how to model a flexibility training in men's artistic gymnastics. A questionnaire was applied to 13 specialists, studying nine variables, which indicates that the most influential variable is the Coaches' Level of Knowledge (NCE), and the most dependent is the Training Model (MoE). The variables training methods (ME) and training techniques (TE) stand out for having high levels of influence and dependence, the resulting variables would be the methodologies observations (MO); individualization (I) and training model (MoE), and the platoon variable the training age (EdE).  It is evident, according to the specialists, the supreme value of the level of knowledge of the coaches on the development of flexibility, being a conditioning factor to be enhanced through improvement courses, guiding the use of the best training methods and techniques to optimally enhance flexibility in men's artistic gymnastics.